Blood DNA methylation marks discriminate Chagas cardiomyopathy disease clinical forms - Brochet, Pauline; Ianni, Barbara; Nunes, João P. S.; Frade, Amanda F.; Teixeira, Priscila C.; Mady, Charles; Ferreira, Ludmila R. P.; Kuramoto, Andreia; Pissetti, Cristina W.; Saba, Bruno; Cândido, Darlan D. S.; Dias, Fabrício; et al. (Frontiers in Immunology, 2022)
Chagas disease is a parasitic disease from South America, affecting around 7 million people worldwide. Decades after the infection, 30% of people develop chronic forms, including Chronic Chagas Cardiomyopathy (CCC), for which no treatment exists. Two stages characterized this form: the moderate form, characterized by a heart ejection fraction (EF) ≥ 0.4, and the severe form, associated to an EF < 0.4. We propose two sets of DNA methylation biomarkers which can predict in blood CCC occurrence, and CCC stage. This analysis, based on machine learning algorithms, makes predictions with more than 95% accuracy in a test cohort. Beyond their predictive capacity, these CpGs are located near genes involved in the immune response, the nervous system, ion transport or ATP synthesis, pathways known to be deregulated in CCCs. Among these genes, some are also differentially expressed in heart tissues. Interestingly, the CpGs of interest are tagged to genes mainly involved in nervous and ionic processes. Given the close link between methylation and gene expression, these lists of CpGs promise to be not only good biomarkers, but also good indicators of key elements in the development of this pathology.